DIETARY INTERVENTION AND NEONATAL BIRTHOUTCOMES & HEALTH STATUS: AN INTERVENTONAL STUDY AMONG GESTATIONAL DIABETIC MOTHERS AT TERTIARY CARE UNITS IN PESHAWAR, PAKISTAN (The Research of Medical Science Review, 2025)
Background: Commonly called as diabetes of pregnancy, Gestational Diabetes Mellitus (GDM) has been linked to adverse fetal-maternal outcomes threatening the life of both mother and fetus and pose a serious risk of perinatal outcomes. The true prevalence of glucose intolerance during pregnancy in Pakistan is still to be determined, However, these mothers need proper dietary interventions for better outcomes both in terms of maternal and neonatal health. Objectives: To analyze the impact of nutritional counseling among GDM mothers the complications associated with delivery outcomes and neonatal health status. Methodology: Target population was the registered cases of pregnant mothers with GDM in Khyber Teaching Hospital, Health Care Center, and Kalsoom Maternity Home Peshawar, Pakistan. Seventy-three gestational diabetic patients were selected for the counseling purpose by through written consent at the Gynae departments of these hospitals. This experimental study was based on counseling procedures, specifically designed diet plan and psychological support. The patients were provided with individualized diet plans based on the specific needs of the mothers either alone or with their prescribed pharmacological therapy and were followed till the termination of pregnancy/Birth. The neonatal birth outcomes were analyzed and compared for the results of diet plan alone and with medications. Results: The present research revealed that dietary intervention either diet alone therapy or diet with insulin therapy exert a positive effect on the reduction of severity of complications associated with the outcome of delivery and neonatal health status. The length of gestation was improved with the dietary intervention. 71.2% patients reached to the full term. The rate of normal vaginal delivery was much high as compared to C-section and instrumental deliveries. 68.5% patients underwent normal vaginal delivery. Similarly, the dietary intervention exhibited a positive effect on the outcome of delivery as 91.8% patients delivered live babies without any injury or birth defect. Health status of the neonates after delivery showed a better improvement in the present research. 94.52% neonates were delivered with normal birth weight that is > 3.0 kg. Similarly, the effect of dietary intervention on the blood glucose levels of the neonates showed that 87.67% neonates were delivered with normal range of blood glucose level. Conclusion: It was observed that appropriate dietary management in gestational diabetes mellitus help reduce hyperglycemia to normoglycemic levels and aids in minimizing the complications linked with delivery outcomes and neonatal health status.